Mediated hugs modulate impressions of Hearsay information. (17th June 2020) - Nakanishi, Junya; Sumioka, Hidenobu; Ishiguro, Hiroshi
ABSTRACT: Direct interpersonal touch affects the recipients' impression of the touch providers and information related to them. However, the applicability of this fact in mediated interpersonal touch remains unclear. In this study, we describe the alleviating effect of mediated interpersonal touch on social judgment and show that mediated hugs with a remote person affect the impression of the hearsay information about a third person. In our experiment, participants rated their impressions via a questionnaire and recall test. Results show that mediated hugs reduced negative inferences when people recalled information about the third person. As a possible underlying mechanism, we argue that stress reduction through mediated hugs moderates negative impressions of the third person. GRAPHICAL ABSTRACT: